The Effect of Ethanol Extract of Purple Eggplant Peel (Solanum Melongena L.) on Estrogen Receptor-Α Levels and Vaginal Epithelium Thickness in a Menopause Model Rat - Yunike Susilo; Ida Ayu Ika Wahyuniari; I Wayan Sugiritama; Ida Sri Iswari; I Wayan Juli Sumadi (Eduvest - Journal of Universal Studies, 2026)
Menopause is a natural phase in a woman's life marked by a decline in estrogen levels, which can lead to various health issues, including vaginal atrophy. One promising alternative treatment is phytoestrogens, such as those found in purple eggplant peel (Solanum melongena L.) extract. This study aims to analyze the effect of administering purple eggplant peel ethanol extract on estrogen receptor-α (ERα) levels and vaginal epithelial thickness in a menopause model rat. The study employed a posttest-only control group design with four groups: a control group (K) and three treatment groups that received the extract at doses of 25 mg/200 g BW, 50 mg/200 g BW, and 100 mg/200 g BW per day for 28 days. The results showed that the 100 mg/200 g BW per day dose significantly increased ERα levels and vaginal epithelial thickness compared to the control group (p < 0.05). The lower doses (25 mg/200 g BW and 50 mg/200 g BW) did not show significant differences from the control group. In conclusion, purple eggplant peel extract at a dose of 100 mg/200 g BW per day can increase ERα levels and vaginal epithelial thickness in menopause model rats, demonstrating its potential as an alternative therapy for menopause symptoms.